Goods Invontory Management System at Nusantara Bakery Company Based on Android - adrian rifwan hakim; Roni Saputra (Ikatan Dosen Menulis, 2024)
The Nusantara Bakery Company is a company operating in the food sector, selling and producing bread. Currently, Nusantara Bakery still uses a conventional data management system for recording production results and recording sales using paper media to record every order and production transaction for sold or expired bread. In the current digital era, the use of Android devices and information technology has become so widespread and efficient. Therefore, this research will design an Android application for processing ordering and production data at the Nusantara Bakery bakery using the waterfall method. The aim of this research is to create an Android application that makes it easier for companies to record production and sales results and makes it easier for sales to order goods. The design of using this application consists of an administrator who makes it easier to manage production data, orders and payments computerized easily using an Android mobile or computer so that the business process runs faster because sales can place orders or request goods directly from the Android mobile application. . Assist leaders in monitoring or evaluating existing business developments at the Nusantra Bakery company.